EVALUASI PROGRAM BEDAH RUMAH DI KECAMATAN PANGKALAN KURAS PEMERINTAH DAERAH KABUPATEN PELALAWAN TAHUN 2015-2016 - Putri, Angela Riazna; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
In an effort to reduce poverty and inequality in villages in Pelalawan District, Pelalawan District government through the Social Service runs a home surgery program starting in 2008. Home surgery is a house or building occupied by poor people whose condition is very poor, built and rehabilitated according to available funds. The purpose of this study were (1) to describe the operation stage house in the subdistrict of Pangkalan Kuras, Pelalawan District. to find out the causes of the house surgery program in Pangkalan Kuras Subdistrict, Pelalawan Regency, it has not been successful. This study uses Hanif Nurcholis's evaluation theory which includes input, process, output, and outcome. This research is a qualitative research. this research was conducted in Pangkalan Kuras District, Pelalawan Regency. The technique used to collect data in the study are (1) interviews, (2) documentation. The results of this study indicate that the first stage of the home surgery program was input, namely from the Social Service to socialize home surgery to the Sub-District Head, after that the Sub-District Head formed a group for the implementation and supervision of the home surgery program. The stages of the process were carried out by selecting recipients of the home surgery program, determining the determination of home surgery, and implementing a home surgery program. Output stages of the implementation of home surgery and the making of accountability reports for the implementation of the home surgery program. outcome sees whether the program has had a real impact on the community. The causes of the home surgery program have not been successful, namely: lack of funding sources, and lack of supporting basic materials, not precisely the target of the home surgery program, there are still many eligible people who have not been touched by housing assistance, supervision is not optimal from the Regional Government.Keywords : Evaluation, Home Surgery Program